Engineering doctorate (EngD) programme at Universiti Teknologi Malaysia - Abd. Majid, Muhd. Zaimi; M. S., Jamiah (2004)
Engineering Doctorate (Eng.D) is a radical alternative to the traditional PhD, being better suited to the needs of industry, and providing a more vocationally oriented doctorate in engineering. The core of the degree is the solution of one or more significant and challenging engineering problem with an industrial context. It provides ambitious and able researchers with the technical, business and personal development competencies needed. In the current context there is a need to produce professional researchers that can enhance Malaysian competitiveness in the construction sector. The focus of this paper is to share our experience in developing Eng.D programme. It discussed a step-by-step process of developing Eng.D programme until obtaining the approval from the Ministry of Education. Through this process we have successfully developed the Eng.D programme and currently there are three EngD candidates following the programme. This Eng.D programme is the first to be approved and conducted in Malaysia. We are confident of producing engineers who are capable of demonstrating innovation in the application of knowledge to the construction sector.